Ladder-shape melting temperature isothermal amplification of nucleic acids - Wang, Deguo (BioTechniques, 2021)
A novel method, termed ladder-shape melting temperature isothermal amplification (LMTIA), was developed in this study. As a proof of concept, one pair of primers or two pairs of nested primers and a thermostable DNA polymerase were employed to amplify the internal transcribed spacer of Oryza sativa with the ladder-shape melting temperature curve. Our results demonstrated that the LMTIA assay with nested primers was 50-fold more sensitive than the LAMP assay with the same level of specificity. The LMTIA method has the potential to be used for the prevention and control of emerging epidemics caused by different types of pathogens